2012
DOI: 10.1177/0218492311420540
|View full text |Cite
|
Sign up to set email alerts
|

Perforation of sinus Valsalva 10 years after repair of ventricular septal defect

Abstract: A 60-year-old woman who underwent ventricular septal defect (VSD) closure, mitral valve repair, and tricuspid annuloplasty 10 years earlier, presented with congestive heart failure. Her previous postoperative echocardiogram demonstrated a residual VSD leak and moderate mitral regurgitation. Transesophageal echocardiography (Figure 1) showed moderate mitral regurgitation, severe tricuspid regurgitation, a large atrial septal defect, and a fistulous communication from the sinus of Valsalva to the right ventricle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In our series, there was no bicuspid valve patients and we found that aortic insufficiency was more severe when the Valsalva aneurysm was ruptured into heart cavities (P = 0.05). In this condition asymmetrical deformity of aortic root rupture of SVA and substantial runoff blood flow in the supra-annular region both can cause severe aortic regurgitation in the absence of a VSD or a notable structural defect in the aortic valve (11). However the cause of AI, when coexist with VSD, is the prolapse of aortic cusp into VSD (12).…”
Section: Discussionmentioning
confidence: 99%
“…In our series, there was no bicuspid valve patients and we found that aortic insufficiency was more severe when the Valsalva aneurysm was ruptured into heart cavities (P = 0.05). In this condition asymmetrical deformity of aortic root rupture of SVA and substantial runoff blood flow in the supra-annular region both can cause severe aortic regurgitation in the absence of a VSD or a notable structural defect in the aortic valve (11). However the cause of AI, when coexist with VSD, is the prolapse of aortic cusp into VSD (12).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we propose that RSVA patients with VSD should have some distinguishing features. Matsushita et al5 reported a rupture of SVA from the right coronary to the right ventricle in a patient whose VSD had closed 10 years prior. A similar case occurred in our study.…”
mentioning
confidence: 99%